Assessment of the physico-nutritional effects and pathogen detection in kangkong (Ipomoea reptans) grown in used vermicomposts-amended soil - Carinal , Limalyn Joy L. (2005.)
The physico-nutritional attributes and presence of pathogens in kangkon (Ipomoea reptans) grown in used Vermicompost-amended soil were assessed in a pot experiment in the greenhouse during late 2004 wet season.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Kangkong; Ipomoea reptans